Performance Analysis Of The Energy Harvesting Techniques In Cooperative Communication Systems of NBIoT Devices With Amplify And Forward (AF) Relaying Protocol - Ines Sastre Umayya; Muhamad Milchan; Hendy Briantoro; Yoedy Moegiharto (Elinvo (Electronics, Informatics, and Vocational Education), 2022)
This study examines the system’s performance with implementation of the energy harvesting (EH) techniques at source node, S and relay node, R. The RF signals which are used to energy harvesting proccess are broadcasted by destination node, D. The information signals from S are sent to D via a R in a cooperative communication framework. The R uses the amplify and forward (AF) protocol to forward the received signal from S to D. We propose a network system which contain of three femto cells, and an access point of each femto cells work as a relay (R), in a macro cell with a base station or eNB as a destination (D). To find the  best R for forwarding the information signal from S to D, we choose the partial relai selection strategy.   From the simulation results can be shown that the throughput system and the outage probability system are affected by the location of S or the distance of between S-R and S-D. Also affected by the access point power of femto cell that is connected to electric source, and  time swithing factor, ρ which is used to harvest energy at S and R nodes. The shorter distance of between S-R and S-D results a better value of  throughput system and the outage probability system, since the gain channel value will be high and increases the SNR value at D. More bigger the power from battery of access point femto cell that is used together with the harvested power by R to forward the signal will result a better value of  throughput system and the outage probability system. More smaller time swithing factor, ρ results more time period for transmitting signal by S and forwarding sinyal by R, therefore increases the transmit power at S and R. Increasing the transmit powers result the increasin SNR value at D, and result a better value of  throughput system and the outage probability system.